Power factor improvement for a three-phase system using reactive power compensation - Majid Ali; Faizan Rashid; Saim Rasheed (Institute of Advanced Engineering and Science, 2021)
For all industrial and distribution sites, the lagging power factor of electrical loads is a common problem. In the early days, it was corrected manually by adding the capacitor banks of certain values in parallel. Automatic power factor correction (APFC) using a capacitor bank helps to make a power factor that is close to unity. It consists of a microcontroller that processes the value of the power factor to enable the system and monitor the power factor if it falls below (0.77) from the specified level. This paper presents the automatic correction of the power factor by adding the capacitors banks automatically of the desired value in a three-phase system in the form of binary coding (0-7). The main purpose of this system is to maintain the power factor as close as to unity, for the experimental case, it is set to (0.93) which helps to decreases the losses and ultimately increase the efficiency of the system.